Understanding and Readiness of Tourism Village Managers in Alamendah: A Study on Accommodating Special Dietary Needs of Tourists - Zakiyah Nur Sholihah; Elly Malihah; Rini Andari (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: The aim of this study is to examine the level of understanding and readiness of the management of Alamendah Tourism Village in accommodating tourists with special dietary requirements. These requirements include dietary restrictions based on religion, food allergies, intolerances, and various lifestyle-based diets. Methodology: The research method employed is a qualitative research method with a descriptive approach. Data collection techniques involved interviews with several managers of Alamendah Tourism Village, including the chairman, secretary, treasurer, and tour guides of Alamendah Tourism Village. Main Findings: The research results indicate that the managers of Alamendah Tourism Village understand and are prepared to accommodate tourists with various types of special dietary needs. However, there are still limitations in the menu items served, as they do not use ingredients prohibited in Islam, such as pork, alcohol, and others, since Alamendah Tourism Village operates under the concept of halal tourism. Novelty/Originality of this study: This study contributes to the literature on community-based tourism by addressing an underexplored aspect: tourists special dietary requirements. It examines the understanding and preparedness of Alamendah Tourism Village managers in accommodating diverse dietary needs, thereby providing practical insights for inclusive tourism management. The findings advance knowledge on integrating visitor dietary preferences into sustainable rural tourism development and community empowerment strategies.